Comparative evaluation of enamel abrasivity by toothbrush and velcro: An in vitro scanning electron microscope study - Ojha, Saroj Kumar (J Indian Soc Periodontol, 2015)
CONTEXT: Plaque control has been shown to be pivotal in maintaining the optimal periodontal health. Mechanical plaque control is the most popular option for establishing the optimal oral health. Toothbrushes have been the novel tool for mechanical cleansing. However, the abrasive potential of the toothbrushes on the enamel surface is an area in gray. AIMS: The aim of this in vitro study is to evaluate the abrasivity of the toothbrush versus the velcro fasteners. MATERIALS AND METHODS: The mounted teeth of both the groups were subjected to abrasion test, and the tooth surfaces were observed for the possible abrasions from the oscillating strokes (toothbrush) and frictional contacts (hook and loop velcro) and examined under the scanning electron microscope. RESULTS: Comparative assessment of both velcro (hook and loop) and toothbrush bristles did not reveal any evidence of abrasion on the tooth specimens. CONCLUSIONS: Veclro fasteners are safe and qualitatively at par to the manual toothbrush for their efficacy and efficiency in teeth cleansing